Media Iklan Menggunakan Aplikasi Adobe After Effek Guna Penunjang Informasi Dan Promosi Di CV. Yuka Production Kota Tangerang - Riswanto Riswanto; Asti Ideliana; Siti Kholipah M (CICES (Cyberpreneurship Innovative and Creative Exact and Social Science), 2017)
The development of computer technology in particular fields of multimedia, visual and audio broadcasting already very rapidly growing at this time as well as the extent of the need for information on the society, the more recent contributions in serving as both a media information advertising and media promotion. Cv. Yuka Production. moves in the field; the service Organizer and Burning, contributing to video shooting and video grafer, is an experienced company in the field of multimedia and became one of the major companies in tangerang. With the aim to introduce the identity and overall information associated therein. Accurate and compelling in terms of the look or content therein. Advertising is any form of message about a product delivered via suatumedia, financed by the proponent are known, as well as addressed to the most atauseluruh of the community. The presentation of the information is packaged in the form of video ads prove very useful for the purpose. Video ads expected this beneficial and could be implemented by CV. Yuka Production.